Istorija Parižskoj Kommuny 1871 goda. [Pri učast. A.Z. Manfreda, E.A. Zelubovskoj, Ja.I. Drazninasa i dr. Pod red. E.A. Želubovskoj, A.Z. Manfreda, M.N. Maškina i dr.] ("Nauka", 1971)
S ukaz. AN SSSR. Institut vseobščej istorii.